Affective Domain Implementation in History Education: A Critical Examination of Pedagogical Practice in Post-Colonial Indonesia - Pipit Widayana; Andy Suryadi; Rizka Cahyaning Arifin Putri; Nurulasyikin Binti Hassan (Indonesian Journal of History Education, 2026)
Abstract: This study critically examines affective domain implementation in Indonesian secondary history education, interrogating persistent disjunctures between policy aspirations and classroom practice. Drawing on qualitative case study research at SMA Negeri 01 Mayong, the investigation reveals that affective learning remains pedagogically peripheral, treated as incidental supplement to cognitive instruction rather than integrated dimension of historical understanding. Teachers conceptualise affective outcomes predominantly through nationalist and behavioural frameworks, overlooking the complex cognitive-affective interplay essential for historical consciousness development. The findings demonstrate that meaningful affective implementation requires reconceptualising history education's purpose in post-colonial societies, moving beyond value inculcation toward cultivating critical historical consciousness that embraces ethical complexity, perspective-taking, and cognitive-affective integration necessary for democratic citizenship.   Abstrak: Studi ini secara kritis mengkaji implementasi ranah afektif dalam pendidikan sejarah jenjang menengah di Indonesia, dengan menginterogasi diskursus yang persisten antara aspirasi kebijakan dan praktik kelas. Berdasarkan penelitian studi kasus kualitatif di SMA Negeri 01 Mayong, investigasi mengungkapkan bahwa pembelajaran afektif tetap berada pada posisi perifer secara pedagogis, diperlakukan sebagai suplemen insidental bagi pengajaran kognitif, alih-alih sebagai dimensi terintegrasi dari pemahaman sejarah. Para guru mengkonseptualisasikan capaian afektif utamanya melalui kerangka nasionalistik dan perilaku, mengabaikan interaksi kompleks antara aspek kognitif dan afektif yang esensial bagi pengembangan kesadaran sejarah. Temuan menunjukkan bahwa implementasi afektif yang bermakna menuntut rekonseptualisasi tujuan pendidikan sejarah di masyarakat pascakolonial, melampaui penanaman nilai menuju pembudayaan kesadaran historis kritis yang merangkul kompleksitas etis, pengambilan perspektif, dan integrasi kognitif-afektif yang diperlukan bagi kewarganegaraan demokratis.